Teaching Portfolios and the Quality Enhancement Project in Higher Education - Timothy Murphy; Iain MacLaren (Educational Futures)
This paper examines the potential of teaching portfolios in higher education for educational development and academic staff promotion purposes. In particular it considers the specific challenges in “research-led” institutions. Given concerns about increasing measures of performance, workload monitoring, the changing nature of academic practice and career progression such work, we believe, is timely and appropriate. There has been a widespread adoption of teaching portfolios as a ‘measure’ of teaching quality (or performance) without due regard to implicit assumptions about their rational, effectiveness and limitations.